EVALUASI KEBIJAKAN PENETAPAN PETA LAHAN SAWAH YANG DILINDUNGI DI KOTA SUKABUMI - Sutisna, Dinar Nur Fadz Niar; Sufianti, Ely; Nurliawati, Nita; Trilestari, Endang Wirjatmi; Dijah, Arundina (Mimbar : Jurnal Penelitian Sosial Dan Politik, 2024)
In 2021, the Minister of Agrarian Affairs and Spatial Planning/National Land Agency issued Ministerial Decree Number 1589/SK-HK.02.01/XII/2021 concerning the Determination of Protected Rice Field Maps. The problem that occurred in Sukabumi City was the inconsistency of the area of Protected Rice Fields between that stipulated according to the Decree of the Minister of Agrarian Affairs and Spatial Planning/National Land Agency and the area designated for food crops in Sukabumi City Regional Regulation Number 1 of 2022. This research is a qualitative research and the research location is in Sukabumi City. Data collection was obtained through observation, documentation, and in-depth interviews with selected informants using William Dunn's evaluation analysis and CATWOE analysis. In testing the validity of the data, a credibility test was used through extended observation, triangulation, and member checks. The results of the study indicate that the policy for Determining Protected Rice Field Maps in Sukabumi City needs to be adjusted.